Trajectory Analysis of Suicidal Ideation in Spanish College Students Using Ecological Momentary Assessment - Layrón Folgado, José Enrique; Conchado Peiró, Andrea; Marco, José H.; Barrigón, María Luisa; Baca-García, Enrique; Pérez Rodríguez, Sandra (Frontiers in Psychiatry, 2022)
Introduction: Suicide is a preventable death in young people. Suicidal ideation commonly underlies suicide, and Ecological Momentary Assessment can help us to better characterize it and its risk and protective factors in the short term. We aimed, first, to investigate the estimated prevalence and trajectories of suicidal ideation in a community sample of Spanish college students using an Ecological Momentary Assessment methodology and, second, explore the associations between risk and protective factors and suicidal ideation categorized as moderate or low. Materials and Method: A total of 737 participants followed the Ecological Momentary Assessment during a period of six months. We estimated the prevalence and trajectories of suicidal ideation and the associations between depressive symptoms, positive and negative affect, thwarted belongingness, perceived burdensomeness, cognitive reappraisal, emotional suppression, and purpose in life with the MEmind smartphone App. Suicidal ideation was assessed 14 times during this period. Results: 28 participants referred to suicidal ideation at least once in longitudinal assessments. We found a lack of curvature and, thus, a relatively stable trajectory of suicidal ideation. Two groups of latent dimensions were observed related to risk and protective factors of suicidal ideation. One latent dimension of the risk factors (higher levels of thwarted belongingness, perceived burdensomeness, depressive symptoms, negative affect, and emotional suppression) best represented the group with moderate levels of suicidal ideation, and a second latent dimension of protective variables (positive affect, cognitive reappraisal, and purpose in life) best represented the group with lower levels of suicidal ideation. Discussion: These findings may indicate that students with a sense of having a life worth living, in addition to having the ability to reevaluate their negative beliefs, are less likely to experience high levels of suicidal ideation. Therefore, purpose in life would be a protective factor against the presence of suicidal ideation.